Effect of family life quality on youth badminton athletes' identity and achievement - Zhu, Dan; Li, Ye-Jun; Tang, Chang-Fa (Frontiers in Psychology, 2025)
IntroductionYoung badminton players who want to achieve certain achievements are faced with inevitable material and mental pressure. Adolescent families can effectively relieve these pressures for them. A large number of studies have demonstrated the influence of family on athlete achievement, but the specific pathways are not clear. The purpose of this study was to explore the impact of family quality of life on the achievement of youth badminton athletes from the perspective of athlete identity.MethodsA total of 111 badminton athletes aged 14–18 (M = 16.27, SD = 1.22) in high school were surveyed using the Athlete Identity Measurement Scale (AIMS) and the Family Quality of Life Scale (FQOL).ResultsThe results show that family quality of life can positively affect athlete achievement. Those athletes who have achieved athletic success generally have better family economic conditions and a harmonious atmosphere of family interaction, but there is a common problem of insufficient psychological care. Secondly, the quality of family life also affects athlete identity. However, there was no significant correlation between the negative affective dimensions in athletes' identification. Third, athlete identity plays a mediating role between family quality of life and athlete achievement.DiscussionOverall, family quality of life is associated with athlete achievement. This study found that the intangible psychological and spiritual care and support of badminton players' families lagged behind the tangible material support. In other words, the family's dedication and support for badminton players should start from the athlete's identity and increase the care at the spiritual level. In addition, there are still some factors that have nothing to do with the quality of life of the family, which need to be dealt with by the athletes themselves. Therefore, parents do not need to be overly anxious about the athletic achievements of their teens.